2013
DOI: 10.3109/10826084.2012.762527
|View full text |Cite
|
Sign up to set email alerts
|

Functioning of Alcohol Use Disorders Criteria Among Middle-Aged and Older Adults: Implications for DSM-5

Abstract: This study explored dimensionality and rank-order severity of the Diagnostic and Statistical Manual of Mental Disorders fourth edition (DSM-IV) alcohol use disorder (AUD) criteria among adults 50+ years old. Secondary analysis was performed on data from individuals 50+ (N = 3,412) from the 2009 National Survey of Drug Use and Health. Confirmatory factor analyses (CFA) and item response theory (IRT) analyses were performed on the 11 AUD criteria. DSM-IV and DSM fifth edition (DSM-5) classifications were compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 49 publications
2
26
0
1
Order By: Relevance
“…As expected, the one-factor model reached good fit indices in the EFA model, as found in other studies using the DSM-5 AUD in large representative samples in the U.S. (Keyes et al, 2011; Kuerbis et al, 2013), Australia (McBride et al, 2011; Mewton et al, 2011) and Israel (Shmulewitz et al, 2010). Keyes et al (2011) and Mewton et al (2011) found a good one-dimensional structure with high values of loadings (> 0.6) for all DSM-5 AUD.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…As expected, the one-factor model reached good fit indices in the EFA model, as found in other studies using the DSM-5 AUD in large representative samples in the U.S. (Keyes et al, 2011; Kuerbis et al, 2013), Australia (McBride et al, 2011; Mewton et al, 2011) and Israel (Shmulewitz et al, 2010). Keyes et al (2011) and Mewton et al (2011) found a good one-dimensional structure with high values of loadings (> 0.6) for all DSM-5 AUD.…”
Section: Discussionsupporting
confidence: 87%
“…Most of the available studies have been carried out in the U.S. (Borges et al, 2010; Keyes et al, 2011; Kuerbis et al, 2013) using exploratory factor analysis (EFA) to validate the DSM-5 AUD unidimensional structure. Evidence from other cultures are much more limited (McBride et al, 2011; Mewton et al, 2011; Shmulewitz et al, 2010) and fewer included the full set of 11 criteria (since some lacked Craving, as defined by DSM-5 Alcohol Use Disorder criteria: Tolerance - as defined by either of the following: (a) a need for markedly increased amounts of alcohol to achieve Intoxication or desired effect; (b) markedly diminished effect with continued use of the same amount of alcohol; Withdrawal - as manifested by either of the following: (a) the characteristic withdrawal syndrome for alcohol (refer to Criteria A and B of the criteria sets for withdrawal from alcohol); (b) alcohol (or a closely related drug such as benzodiazepines) is used to relieve or avoid withdrawal criteria; Larger/Longer - alcohol is often used in larger amounts or over a longer period than was intended; Quit/Control - there is a persistent desire or unsuccessful efforts to cut down or control alcohol use; Time Spent - a great deal of time is spent in activities necessary to obtain alcohol, use alcohol, or recover from its effects; Activities Given Up - important social, occupational, or recreational activities are given up or reduced because of alcohol use;Physical/Psychological - alcohol use is continued despite knowledge of having a persistent or recurrent physical or psychological problem that is likely to have been caused or exacerbated by alcohol (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…86 The findings revealed that there were differential responses among older versus middle-aged adults, such that older adults were half as likely as middle-aged adults to endorse the criteria related to tolerance, activities to obtain alcohol, social/ interpersonal problems, and physically hazardous situations. The criteria that were most successful in discriminating AUD among older adults were unsuccessful efforts to cut back, withdrawal, and social and interpersonal problems.…”
Section: Diagnosismentioning
confidence: 96%
“…Furthermore, interruption in social and vocational roles or other consequences of drinking or drug use may be less likely to occur or less noticeable in old age. 44,86 Aging is often associated with a natural departure from these roles, such as through retirement 78 or social isolation caused by mortality of age-group peers. 87 Furthermore, the criterion related to continued use despite persistent or recurrent problems may not apply to many older adults who do not recognize that their problems, such as depression, are related to drinking.…”
Section: Diagnosismentioning
confidence: 99%
See 1 more Smart Citation